Computational Analysis of the Influence of Dissolution-Diffusion and Specific Binding on Drug Transport in the Arterial Wall following Stent-based Delivery - Escuer Gracia, Javier; Peña Baquedano, Estefanía; McGinty, Sean; Martínez, Miguel Ángel (Jornada de Jóvenes Investigadores del I3A, 2018)
A computational model of the transport of drugs eluted from a drug-eluting stent (DES) in the arterial wall is developed to study the influence of considering a non-linear model of dissolution-diffusion in the polymeric strut coating of the stent and a non-linear saturable reversible reaction model in the tissue to describe drug specific and non-specific binding.